Effect of Dexmedetomidine on the ED50 and ED95 of Sufentanil in Patient-Controlled Intravenous Analgesia After Cesarean Section: A Randomized, Controlled, Double-Blind Trial - Li J; Fu W; Wang N; Zeng S; Li X; Wan J; Wang F (Drug Design, Development and Therapy)
Jiabei Li,1,2 Wuchang Fu,3 Na Wang,1 Sisi Zeng,1 Xuechao Li,1 Jixiang Wan,1 Fangjun Wang1 1Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, Nanchong, People’s Republic of China; 2Department of Anesthesiology, Meishan City People’s Hospital, Meishan, People’s Republic of China; 3Department of Anesthesiology, The Second Clinical Medical College of North Sichuan Medical College (Nanchong Central Hospital), Nanchong, People’s Republic of ChinaCorrespondence: Fangjun Wang, Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, No. 1 Maoyuan South Road, Nanchong, Sichuan, 637000, People’s Republic of China, Tel +86 13458253172, Email wfjlxy006@126.comPurpose: To determine the effect of dexmedetomidine on the ED50 and ED95 of sufentanil in patient-controlled intravenous analgesia (PCIA) after cesarean section.Patients and Methods: Parturients who underwent elective cesarean section (n = 80) were randomly assigned to either the sufentanil group (S group) or the dexmedetomidine-sufentanil combination group (DS group). Patients in the S group received a combination of sufentanil, 5 mg of tropisetron, and saline, whereas patients in the DS group were administered 1.5μg/kg of dexmedetomidine in addition to sufentanil, 5 mg of tropisetron, and saline. The ED50 and ED95 of sufentanil were determined by Dixon sequential method. We used probit regression to calculate the ED50, ED95, and 95% confidence intervals for sufentanil in each group.Results: The ED50 and ED95 for sufentanil in the S group were 1.634 (95% CI: 1.476– 1.810)μg/kg and 2.035 (95% CI: 1.841– 3.312)μg/kg, respectively. The ED50 and ED95 for sufentanil in the DS group were 1.275 (95% CI: 1.187– 1.353)μg/kg and 1.503 (95% CI: 1.406– 1.824)μg/kg. The VAS scores with rest at t5 and with movement at t4- t5 were lower in the DS group (P< 0.05). The t2-t5 Ramsay scores in the DS group were higher than those in the S group (P< 0.05). The doses of sufentanil and tramadol were markedly reduced in the DS group, while the onset of first lactation occurred significantly earlier in the DS group (P< 0.05). Compared with the S group, the DS group had a lower incidence of nausea, vomiting, and skin itching (P< 0.05), and lower frequency of patient-controlled analgesia (PCA) episodes (P< 0.05), and better postoperative pain satisfaction (P< 0.05).Conclusion: The 1.5μg/kg dexmedetomidine can significantly decrease the ED50 and ED95 of sufentanil in patient-controlled intravenous analgesia after cesarean section, provide good postoperative analgesia and sedation, and promote the earlier occurrence of first lactation.Keywords: dexmedetomidine, sufentanil, cesarean section, postoperative analgesia, ED50, ED95